Respostas

2013-06-02T23:12:32-03:00

A fórmula que usamos é D(A,B)=\sqrt{({x_{2}-x_{1})^2+(y_{2}-y_{1})^2}

A) D(A,C)=\sqrt{(-7-3)^2+(0-9)^2}=>\sqrt{(-10)^2+(-9)^2}=>\sqrt{100+81}=>D(A,C)=\sqrt{181}

 

B)D(D,M)=\sqrt{(\frac{8}{2}-\frac{1}{2})^2+(-6+1)^2}=>\sqrt{(\frac{7}{2})^2+(-5)^2}=>\sqrt{\frac{49}{4}+25} => \sqrt{\frac{149}{4}}=> D(D,M)=\frac{\sqrt{149}}{2}}

 

C)D(T,H)=\sqrt{(2-\sqrt{6})^2+(-4-2)^2}=> \sqrt{4-4\sqrt{6}+6+(-6)^2}=> \sqrt{10-4\sqrt{6}+36} =>> D(T,H) = \sqrt{46-4\sqrt{6}}

 

D)D(J,L) = \sqrt{(8-0)^2+(-6-0)^2}=> \sqrt{(8)^2+(-6)^2}=> \sqrt{64+36}=> \sqrt{100} =>D(J,L) = 10

 

Qualquer dúvida, pode perguntar por mensagem. Um abraço ai ;)

5 4 5